2010
DOI: 10.1111/j.1749-8198.2010.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Economic Development: A Review of the Literature from Industrialized Economies

Abstract: Over the past 30 years, accelerating change has been one of the defining attributes of rural landscapes around the world. In response, there has been an increasing volume of rural economic development research and public/policy interest in that research. The purpose of this review article is not to provide a ‘state of the literature’ summary, but rather to highlight thematic directions, opportunities, and trends in the rural economic development literature over the past decade in industrialized economies. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 146 publications
(225 reference statements)
1
30
0
Order By: Relevance
“…The study crosses a number of themes identified by Ryser and Halseth (2010) in their overview of rural economic development research (see Table 1, p. 512). Following a review of literature on rural resilience and rural communities from an interactional perspective, we introduce the two case studies, present the research methods, provide quantitative and qualitative findings from our research and then review these results in relation to resilience in rural communities.…”
Section: Introductionmentioning
confidence: 99%
“…The study crosses a number of themes identified by Ryser and Halseth (2010) in their overview of rural economic development research (see Table 1, p. 512). Following a review of literature on rural resilience and rural communities from an interactional perspective, we introduce the two case studies, present the research methods, provide quantitative and qualitative findings from our research and then review these results in relation to resilience in rural communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing huge regional differences in geographical background, bio-geo-physical conditions, and socio-economic development base and other factors made the transformation show significant regional differences, and the agriculture and rural development state shows significant regional differences too (Li and Wei 2010;. All these discrepancies presented a great challenge for the formulation and implementation of agricultural and rural development policies, which needs understanding the specific development constraints and options of various regions (Courtney et al 2006;Ryser and Halseth 2010;Long et al 2010). …”
Section: Theoretical Contextmentioning
confidence: 99%
“…Moreover, the wide spatial variation in local attribute can also thwart "one size fits all" personbased policies (Partridge and Richman 2006). There is a need for more effective, place-based policies which can better capture the diverse challenges and potential of rural areas (OECD 2003;Bridger and Theodore 2008;Ryser and Halseth 2010).…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Haugland, Ness, Gronseth, andAarstad (2011) argued that individual communities could gain a lot by working with surrounding communities to generate ideas, create a larger destination identity and integrate experiences within the region. A destination identity is very important, as NBT industries are place-oriented making the local and regional landscape, and community a key part of the packaged tourist experience (Ryser & Halseth, 2010).…”
Section: Economic Transition and The Emergence Of Post-productive Indmentioning
confidence: 99%